Legal Responsibility of Orthopedic Physicians Towards the Authority to Assess Disability and Assess Return to Work in Workers with Extremity Disabilities Due to Work Accidents - Henry Ricardo Handoyo; Mokhamad Khoirul Huda (Journal of Law, Politic and Humanities, 2025)
This study analyzes the legal responsibility of orthopedic doctors in assessing disability and return to work fitness for workers with limb disabilities due to work accidents. The focus of this study includes aspects of legal regulation, medical ethics standards, and the legal implications of negligence in assessment practices. The analysis was conducted based on Article 46 of Law No. 44 of 2009 concerning Hospitals and the principle of vicarious liability, which highlights the importance of hospital responsibility for the actions of doctors operating under their supervision. This aims to protect patients and minimize the risk of litigation. The method used in this study is normative juridical with a descriptive-analytical approach. This study emphasizes the importance of clear communication and comprehensive documentation in medical practice as part of efforts to prevent negligence. The results of the study indicate that the application of strict professional standards and ongoing training can strengthen legal protection for orthopedic doctors. In addition, this also has the potential to increase patient trust in medical practice. Thus, this study contributes to the understanding of legal and ethical responsibility in the context of treating patients with disabilities due to work accidents.